MINERALOGICAL AND GEOCHEMICAL PROPERTIES OF HYDROTHERMAL ALTERATIONS: DARIDERE AREA, ISPARTA, SW TURKEY - Onal, Betul Coskun; Cengiz, Oya (Stef92 Technology Ltd, 2014)
In the study area, the volcanic rocks of Miocene-Pliocene Golcuk formation have undergone intense alteration. Due to alteration, the rocks have become losing primary compositions and have an appearance of gray, white, beige, brown, and greenish-yellow. Alteration types of the study area are argillation, alunitization, silicification, and limonitization. Mineral contents of the alterations are feldspar, illite, simectite, kaolinite, jarosite, quartz, amorphous silica, opal, dolomite, hematite, limonite, pyrite, gypsum, and calcite. The alterations show the enrichment for Al2O3, Na2O, and K2O. Mineralogical analyses indicate that high values may be come from feldspar, illite, kaolinite and zeolite of Al2O3, feldspar and clay minerals of Na2O and K2O, opal, quartz and amorphous silica of SiO2. Ba-Sr, Ni-Co and Pb-Cu-Zn-As contents of the alterations have a weak enrichment. The mineral assemblage and trace element contents of alterations suggest the solutions of hydrothermal origin. The alterations have derived from commonly felsic and locally mafic volcanic rocks of Golcuk formation. In addition, it may be considered as enriching on locations of volcanic rocks that the elements such as Ba, Sr, Ni and Co from basic-ultrabasic rocks of Gokcebag Complex, transporting by various effects.
14th International Multidisciplinary Scientific Geoconference (SGEM) -- JUN 17-26, 2014 -- Albena, BULGARIA
Keywords: Isparta-Turkey; hydrothermal alteration types; mineral content; element enrichments; original rocks